2013
DOI: 10.1108/jmh-07-2012-0052
|View full text |Cite
|
Sign up to set email alerts
|

Exploring early academic responses toFunctions of the Executive

Abstract: Purpose – This paper aims to deepen understanding of the influence of Barnard's Functions of the Executive in management theory by examining its early scholarly reception. Design/methodology/approach – The research presented is a qualitative analysis of references to Barnard's work in academic journals prior to 1956, based on 139 articles identified through text-based searching of electronic databases. Findings – Favorable opinions of Barnard's book tend to emphasize his practical insights as a busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…In my review, I found that the greatest number of articles referenced Chester I. Barnard and his influence on the executive in management theory (Isomura, 2010;Malcolm and Hartley, 2010;Fernández, 2010;Novicevic et al, 2011aNovicevic et al, , 2011bNovicevic et al, , 2013Singleton, 2013). In both Wren and Hay's (1977) review, in addition to Heames and Breland's (2010) review, Chester I. Barnard was one of the top three most studied management pioneers.…”
Section: Management Pioneers and Founders Of The Disciplinementioning
confidence: 86%
“…In my review, I found that the greatest number of articles referenced Chester I. Barnard and his influence on the executive in management theory (Isomura, 2010;Malcolm and Hartley, 2010;Fernández, 2010;Novicevic et al, 2011aNovicevic et al, , 2011bNovicevic et al, , 2013Singleton, 2013). In both Wren and Hay's (1977) review, in addition to Heames and Breland's (2010) review, Chester I. Barnard was one of the top three most studied management pioneers.…”
Section: Management Pioneers and Founders Of The Disciplinementioning
confidence: 86%